Performance of Indonesian state owned enterprises, managerial performance vs. financial performance - Arifah; Rahmawati; Nur Probohudono Agung; Setianingtyas Honggowati; Kiswanto (Global Business & Finance Review (GBFR), 2023)
Purpose: This study aims to provide more detailed knowledge of how the performance of Indonesian SOEs is described from the perspective of managerial performance and financial performance. Design/methodology/approach: The method used in this study is comparative analysis where managerial performance is measured using the KPKU score and financial performance is measured using profitability ratios. Comparative analysis is carried out in detail per year and per SOE sector. Findings: This study found that in general from a managerial performance standpoint, the performance of Indonesian SOEs showed an increase while from a financial performance perspective, the performance of Indonesian SOEs showed a decline. This is because the determination of managerial performance is assessed in a more complex manner, including the level of public services provided to the public. Research limitations/implications: The limitations of this study have not been able to describe in detail each score of the components in managerial performance appraisal, which can be considered for further research in the future. This research implies that all parties must be careful in assessing the performance of SOE because the measurement of performance using managerial and financial measures can be different. Originality/value: The originality of this research is to provide a comparative picture of SOE as a whole which has never been done before. This research contributes to the government as a regulator to try to further improve financial performance so that it can be more in sync with the increase in managerial performance, so that both managerial performance appraisal and financial performance appraisal can provide directions that are close to parallel.
Keywords: 650; Performance; Managerial; Financial; SOE